Nonalcoholic beer reduces inflammation and incidence of respiratory tract illness - Scherr, J.; Nieman, D. C.; Schuster, T.; Habermann, J.; Rank, M.; Braun, S.; Pressler, A.; Wolfarth, B.; Halle, M. (Medicine & Science in Sports & Exercise, 2012)
Purpose: Strenuous exercise significantly increases the incidence of upper respiratory tract illness (URTI) caused by transient immune dysfunction. Naturally occurring polyphenolic compounds present in food such as nonalcoholic beer (NAB) have strong antioxidant, antipathogenic, and anti-inflammatory properties.